Pendampingan Gemari dan Redarkum Melalui Diseminasi “Stop Pernikahan Dini” - Lila Pangestu Hadiningrum; Diana Zuhroh; Fairuz Sabiq (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
Indonesia is faced with increasing cases of early marriage globally. It is necessary to socialize the minimum age limit and the maturity of the marriage age as an insight to the community and awareness to teenagers so that in planning a family by considering various aspects related to married life. This study raises the priority issues used related to the lack of literacy related to the Marriage Age Limit in Pucang Miliran Village, Tulung, Klaten. Assistance for gemari and redarkum through the dissemination of "stop early marriage" is a priority for bottom-up programs that promote public and youth awareness. The model used in this mentoring is community participation (especially parents and youth). Lectures and discussions are used as methods in the implementation of mentoring through dissemination activities and efforts that can be made by teenagers to prevent early marriage. In this assistance, it becomes a community-based program that aims to prevent child marriage with activities in the program including increasing awareness of adolescents and the community, peer educators, hearings through the media, and collaboration. The need for follow-up activities in collaboration with non-formal and formal institutions in maturing the age of marriage and productive training for adolescents.